WAIS Divide Microparticle Concentration and Size Distribution, 0-2400 ka - Koffman, Bess; Kreutz, Karl (IEDA: US Antarctic Program Data Center, 2015)
Abstract: This data set includes raw dust microparticle data for the WAIS Divide deep core, WDC06A, from the surface to 577 m. Data were collected in 2010 using a Klotz Abakus laser particle counter connected to a continuous ice core melter system at the University of Maine (Breton et al., 2012).